Immune‐mediated ECM depletion improves tumour perfusion and payload delivery - Yen Ling Yeow; Venkata Ramana Kotamraju; Xiao Wang; Meenu Chopra; Nasibah Azme; Jiansha Wu; Tobias D Schoep; Derek S Delaney; Kirk Feindel; Ji Li; Kelsey M Kennedy; Wes M Allen; et al. (EMBO Molecular Medicine)
Abstract High extracellular matrix (ECM) content in solid cancers impairs tumour perfusion and thus access of imaging and therapeutic agents. We have devised a new approach to degrade tumour ECM, which improves uptake of circulating compounds. We target the immune‐modulating cytokine, tumour necrosis factor alpha (TNFα), to tumours using a newly discovered peptide ligand referred to as CSG. This peptide binds to laminin–nidogen complexes in the ECM of mouse and human carcinomas with little or no peptide detected in normal tissues, and it selectively delivers a recombinant TNFα‐CSG fusion protein to tumour ECM in tumour‐bearing mice. Intravenously injected TNFα‐CSG triggered robust immune cell infiltration in mouse tumours, particularly in the ECM‐rich zones. The immune cell influx was accompanied by extensive ECM degradation, reduction in tumour stiffness, dilation of tumour blood vessels, improved perfusion and greater intratumoral uptake of the contrast agents gadoteridol and iron oxide nanoparticles. Suppressed tumour growth and prolonged survival of tumour‐bearing mice were observed. These effects were attainable without the usually severe toxic side effects of TNFα.